Pengaruh Penggunaan Metode Jarimatika Terhadap Literasi Numerasi Melalui Program Kampus Mengajar Batch 5 di Sekolah Dasar - Jumadiyah, Nabila; Zumrotun, Erna (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Improving numeracy literacy is the national agenda of the Indonesian Nation in the educational aspect. This is motivated by the results of the PISA research in 2018, which explained that the numeracy literacy of Indonesian people is still relatively low. The Jari Matika method is an alternative solution that can be used to solve this problem because it is simple and easy to apply to elementary school-aged children. This research itself aims to determine the effect of using the Jari Matika method on the numeracy literacy of students at SD Negeri 5 Mindahan through the Kampus Mengajar Batch 5. The research method used is quantitative with an experimental approach. The average score of students before being given treatment was 27.89, while the average score after students were given treatment was 70.26. From the results of the t-test analysis, it can be seen that the sig. (2-tailed) value of 0.000<0.05. Through these results, it can be concluded that there is an enhancement in students’ numeracy literacy before and after being given treatment, which in the research is the use of the Jari Matika method.